2022
DOI: 10.1111/apt.17308
|View full text |Cite
|
Sign up to set email alerts
|

Vigorous physical activity provides protection against all‐cause deaths among adults patients with nonalcoholic fatty liver disease (NAFLD)

Abstract: Summary Background Mortality benefits of vigorous leisure time physical activity (LTPA) among adults with NAFLD is not known. Aim To investigate association between LTPA and reduction in all‐cause mortality among adults with NAFLD. Methods We used NHANES (1999–2006) self‐reported PA data for adults (≥40 years) with mortality follow‐up through December 31, 2015. US‐Fatty Liver Index in absence of secondary causes identified NAFLD. Moderate and vigorous LTPA were calculated by the 2018 PA Guidelines for American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 65 publications
0
22
1
Order By: Relevance
“…In addition, this benefit was achieved when NAFLD subjects achieved at least 150 min of exercise but no more than 299 min of physical activity and at least 50% of their time was spent participating in vigorous activity. 2 The recommendation that 2 minutes of moderate activity can count as 1 minute of vigorous activity was not observed in our study. 5 Nevertheless, we recommend further exploration and research in this area.…”
Section: N V I T E D E D I T O R I a L Editorial: Let's Get Physical-...contrasting
confidence: 54%
See 3 more Smart Citations
“…In addition, this benefit was achieved when NAFLD subjects achieved at least 150 min of exercise but no more than 299 min of physical activity and at least 50% of their time was spent participating in vigorous activity. 2 The recommendation that 2 minutes of moderate activity can count as 1 minute of vigorous activity was not observed in our study. 5 Nevertheless, we recommend further exploration and research in this area.…”
Section: N V I T E D E D I T O R I a L Editorial: Let's Get Physical-...contrasting
confidence: 54%
“…However, notably our results indicated that vigorous activity, not moderate activity, was associated with a mortality benefit. In addition, this benefit was achieved when NAFLD subjects achieved at least 150 min of exercise but no more than 299 min of physical activity and at least 50% of their time was spent participating in vigorous activity 2 . The recommendation that 2 minutes of moderate activity can count as 1 minute of vigorous activity was not observed in our study 5 .…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…In a recent edition of Alimentary Pharmacology & Therapeutics , Henry et al 8 performed a longitudinal analysis of over 5000 adults from the National Health and Nutrition Examination Survey (NHANES) in which they examined the association between leisure‐time PA and mortality in patients with NAFLD, with particular attention to vigorous intensity PA. While vigorous‐intensity PA was reported by ~25% of the study population over the 12+ year follow‐up period, this intensity conferred a 56% lower risk of all‐cause mortality and a 79% reduction in cancer‐related mortality for individuals with NAFLD who spent at least 50% of their total PA engaged in vigorous activity, confirming a recent population‐based report about the association between vigorous PA and hepatocellular carcinoma in ¾ a million patients 9 .…”
mentioning
confidence: 99%